Ẓuhūru al-Adab al-Roqmy ka Waṡīlah al-A’māl al-Adabiyah fī ‘Aṡr al-Alfiyah - Anita Andriya Ningsih; Muhammad Mubasysyir Munir; Mustapa Mustapa Mustapa (Arabic Language and Letters Department, 2021)
The scope of cyber literature in various works convey through electronic media that is overgrowing today. The position of cyber literature in cutting-edge literary research is a region of study. And cyber literature presents a phenomenon full of uniqueness, creativity, and full of challenges for academic researchers. Studies are scholarly research with literature studies obtained from various sources. The phenomenal development of Arabic literature on the internet is the work of King Al-Sana with the title Girls of Riyadh, which is a best seller because of its controversial content and language used simply and with the internet helps the promotion process without the limits of space and time. Exploration of online literary works in various forms of literary works can be widely enjoyed through web links complete with references and literary biographies.